2022
DOI: 10.3390/smartcities5010022
|View full text |Cite
|
Sign up to set email alerts
|

Technology Developments and Impacts of Connected and Autonomous Vehicles: An Overview

Abstract: The scientific advancements in the vehicle and infrastructure automation industry are progressively improving nowadays to provide benefits for the end-users in terms of traffic congestion reduction, safety enhancements, stress-free travels, fuel cost savings, and smart parking, etc. The advances in connected, autonomous, and connected autonomous vehicles (CV, AV, and CAV) depend on the continuous technology developments in the advanced driving assistance systems (ADAS). A clear view of the technology developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Research has shown that CAV communications are of undeniable importance. The current state of the art shows that the evolution of these connected autonomous vehicles (CAVs) in terms of vehicle-to-vehicle (V2V) communication is very well developed with a wide range of vehicle-to-infrastructure (V2I) implications [ 73 ].…”
Section: Autonomous Vehiclesmentioning
confidence: 99%
“…Research has shown that CAV communications are of undeniable importance. The current state of the art shows that the evolution of these connected autonomous vehicles (CAVs) in terms of vehicle-to-vehicle (V2V) communication is very well developed with a wide range of vehicle-to-infrastructure (V2I) implications [ 73 ].…”
Section: Autonomous Vehiclesmentioning
confidence: 99%
“…Object detection algorithms for AVs focus primarily on road signs, pedestrians, cyclists, or other vehicles (eg Jahromi et al 2019;Rosique et al 2019;Ahmed et al 2022), with comparatively fewer methods designed for animal detection (Sharma and Shah 2017;Munian et al 2020;Saxena et al 2020). The high levels of morphological variation across species, along with a wide range of sensory perception processes, behavioral responses, and means of locomotion, introduce several obstacles to automated animal detection methods.…”
Section: Integrating Conservation Into Autonomous Vehicle Research Ob...mentioning
confidence: 99%
“…One of the technological factors that can have a significant impact on emergency vehicle driving is the use of GPS and navigation systems. These systems can provide real-time updates about traffic conditions and route emergency vehicles around congestion or other obstacles, helping to ensure that they can reach their destination as quickly and efficiently as possible [8,9]. Another important technological factor is vehicle-to-everything communication, which enables vehicles to communicate with each other and with infrastructures, such as traffic signals and parking garages.…”
Section: Introductionmentioning
confidence: 99%